Functional features of dispatching control centre for automatic control system of agricultural enterprise - Lytvynov, V.V.; Mykhailiuk, I.V.; Posadska, A.S. (Математичні машини і системи, 2014)
The problems of construction of dispatching control system for agricultural enterprise are investigated. The selection of the functionality of dispatching control subsystem, which allows minimizing losses associated with low-quality and untimely implementation of issues of executive plan is considered in the article. The task of providing timely and qualitative response to unforeseen events is presented.